Utility of multiplex real-time polymerase chain reaction for the detection of bacteria from sputum samples of community acquired pneumonia patients: A study from Dhaka, Bangladesh - Afroz, Sonia; Alam, Fatema Mohammad; Saleheen, Rafique Us; Arafat, Md Yasir; Paul, Rupash; Khatun, Aysha; Sajid, Khandaker Md. Tasnim; Sattar, Abu Naser Ibne; Miah, Md Ruhul Amin (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: This study was carried out to evaluate the utility of multiplex real-time polymerase chain reaction (PCR) to identify the common bacterial agents of community acquired pneumonia (CAP). Methods: Sputum and blood samples were collected from 80 clinically suspected CAP patients in three tertiary-level hospitals in Dhaka city. Multiplex real-time PCR assay was carried out to simultaneously detect five common bacterial agents of CAP; Streptococcus pneumoniae, Haemophilus influenzae, Mycoplasma pneumoniae, Chlamydophila pneumoniae, and Legionella pneumophila. Routine microbiological methods and serology were carried out. The results of PCR were compared with culture, Gram stain and serology. Results: Among the 80 patients, sputum samples of 35 (43.7%) patients were positive by PCR, of which the most commonly detected bacteria were S. pneumoniae (25/35, 71.4%), followed by H. influenzae (9/35, 25.7%) and L. pneumophila (1/35, 2.9%). All 80 sputum samples were negative for both M. pneumoniae and C. pneumoniae by PCR. Out of the 26 culture positive sputum samples, 8 (30.7%) were positive for S. pneumoniae and 1 (3.8%) was positive for H. influenzae. Among the 52 Gram stain valid sputum samples, 24 (46.1%) were S. pneumoniae and 7 (13.5%) were H. influenzae. By serology, out of the 80 cases, M. pneumoniae was detected in 32 (40%) and C. pneumoniae in 24 (30%) of cases. Mixed infections comprised of 38.8% (31/80) cases. Conclusion: Multiplex real-time PCR is useful for the rapid and simultaneous detection of bacterial pathogens of CAP in sputum and can help support traditional laboratory methods for the accurate diagnosis of CAP patients.